Students’ Toxic Friendship Behavior Survey: Challenges To Creating A Healthy Learning Environment - Dian Oktary; Isnaria Rizki Hayati; Khairiyah Khadijah; Putri Yuningsih (INSIGHT: Jurnal Bimbingan Konseling, 2026)
Toxic friendship behavior among students is on the rise and has the potential to undermine the quality of social interactions and the learning environment. This situation poses a serious challenge to creating a healthy and conducive learning environment in schools. This study aims to comprehensively analyze the prevalence of toxic friendship behavior and evaluate its relationship with the quality of the students’ learning environment. The research subjects were students at a high school in Pekanbaru selected through stratified random sampling. The study employed a quantitative approach using a structured questionnaire-based survey method. Data analysis was conducted using descriptive and inferential statistics, including percentage calculations and correlation tests. The results indicate that toxic friendship behavior falls into the moderate category, with a tendency to negatively impact social interactions and learning comfort. It is concluded that toxic friendship contributes to a decline in the quality of the learning environment. The implications of this study underscore the urgency of strengthening preventive guidance and counseling services in schools.